Fanti Kinship and the Analysis of Kinship Terminologies - Kronenfeld, David B. (University of Illinois Press, 2008)
This book examines Fanti kinship terminology from a variety of analytic and formal perspectives. Based on work with a broad number of informants, David B. Kronenfeld details and analyzes internal variation in usage within the Fanti community, shows the relationship between terminology and social groups and communicative usage, and relates these findings to major theoretical work on kinship and on the intersections of language, thought, and culture. The terminological analysis in this study employs a great variety of formal approaches, assesses the strengths and weaknesses of each approach, and covers a wide range of types of usage. This work also performs a systematic, formal analysis of behavior patterns among kin, joining this approach with the analysis of a kinship terminological system. Rather than treating kinship terminology as a special, isolated piece of culture, this study also ties its analysis to more general semantic and cultural theoretical issues. Including computational and comparative studies of kinship terminologies, this volume represents the fullest analysis of any kinship terminological system in the ethnographic record.
Electronic book.
Keywords: Fanti (African people) -- Social life and customs.; Kinship -- Ghana.; Families -- Ghana.; Language and culture -- Ghana.; Ghana -- Social life and customs.; Fanti (Peuple d'Afrique) -- Mœurs et coutumes.; Parenté -- Ghāna.; Familles -- Ghāna.; Langage et culture -- Ghāna.; Sociolinguistics.; Linguistics.; LANGUAGE ARTS & DISCIPLINES.; Cultural.; Anthropology.; Marriage & Family.; Sociology.; Electronic books.